Secure topology protocol for mobile peer-to-peer networks - LI Zhi-yuan1; WANG Ru-chuan1 (Tongxin xuebao)
For the security problem in mobile peer to peer（MP2P） networks,an adaptive mobile peer-to-peer secure topology protocol（AMPSTP） was proposed.Firstly,Fortune algorithm was used to divide a large geographical region into some small sub regions.Secondly,temporary anchor node selection and update strategies were given.Thirdly,MP2P overlay network topology construction and maintenance mechanisms were also given.Fourthly,MP2P overlay network routing discovery algorithm and node selection mechanism based on game theory for MP2P networks were successively proposed.Finally,the performance of the AMPSTP protocol was theoretically analyzed and simulated on the platform of NS-2.Theoretical analysis and simulation results show that compared with MADPastry protocol,AMPSTP protocol not only can guarantee the network security and improve network performance,but also greatly reduce the control overhead.